Clinical scales in autoimmune encephalitis—A retrospective monocentric cohort study - Stefan Macher; Gabriel Bsteh; Romana Höftberger; Thomas Berger; Paulus Rommer; Tobias Zrzavy (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Assessing severity of antibody‐mediated encephalitis (AE) or paraneoplastic encephalitis (PE) requires valid and reliable scores to guide treatment decisions and predict outcome both in clinical routine and studies. We aimed to validate the prognostic value of the clinical assessment scale in autoimmune encephalitis (CASE) and the anti‐NMDAR‐encephalitis one‐year functional status (NEOS) score in patients suffering from AE and PE in a large monocentric cohort. Methods We retrospectively applied the CASE and NEOS score to patients with definite AE and PE treated at a tertiary hospital. Correlations were established between the CASE and NEOS score and the modified Rankin scale (mRs). Multivariable analyses were calculated to identify predictors of outcome. Results Thirty‐four patients (27 AE, 7 PE) were included. Correlations between mRS and CASE score were strongest in patients with AE compared to PE at all intervals, but in the subgroups (LGI1, NMDAR, GAD, miscellaneous surface antibodies, PE) the correlation was strongest in the interval after baseline. Patients with AE seemed to display better outcomes compared to PE, which was underlined by multivariable analysis. Improvement was mostly observed within 6–12 months after disease onset, after which little or no further improvement was noted with some exception for two patients with anti‐NMDARE who recovered substantially even after 12 months of treatment. The NEOS score significantly predicted the outcome at last follow‐up in patients with AE with a sensitivity of 79% at a cut‐off value of 2 points (AUC 0.79, 95% CI 0.58–0.99, p = 0.04). Interpretation The CASE and NEOS score are suitable supplementary tools in addition to the mRS for capturing diverse symptoms, for grading and monitoring symptom severity.